Navigating Influenza outbreaks in the aftermath of COVID-19: safeguarding the UiTM Seremban community / Dr. Farah Adilla Ab Rahman and Jeniwaty Mohd Jody - Ab Rahman, Farah Adilla; Mohd Jody, Jeniwaty (Universiti Teknologi MARA, Negeri Sembilan, 2023)
The global battle against COVID-19 has reshaped our perceptions of infectious disease outbreaks and the crucial need for effective containment strategies (Leach et al., 2021). As we continue to grapple with the ongoing COVID-19 pandemic, it is imperative that we remain vigilant against other contagious diseases, such as influenza (Chotpitayasunondh et al., 2021). This article delves into the transmission dynamics of influenza, especially concerning the UiTM Seremban Campus, while proposing comprehensive measures to ensure the safety of both students and staff in the face of potential influenza outbreaks.